Les conventions locales pour la gestion des ressources naturelles au Sénégal : Entre autonomisation et problème d’appropriation - El hadj Touré (VertigO)
The local conventions can be defined as justifiable agreements negotiated between several stakeholders in a perspective of natural and environmental resources regulation - in terms of control, access, appropriation, usage and exploitation. In Sahel, although they are fashionable and enjoy more attention at the decision-makers, these instruments are still poorly considered in the current context of the decentralization (Diallo, 2003), like plans of occupation and affectation of grounds (POAS) experimented in the valley of the Senegal River. The aim of this paper is to question, from a survey led in a rural district with elected representatives, with technicians, with associative persons in charge and with users, the impact of this informal system, although formalized, of joint land management. The POAS, contributed to strengthen the capacities of the local elected representatives to act in their space, and farmers users to deliberate collectively on a stake so crucial as the agropastoral land tax. It was not however the object of an effective appropriation on behalf of these elected representatives in charge of its application, and these supposed users to follow the agreed operational rules. Between empowerment and problem of appropriation, the local conventions are left by tools necessary for a management shared by the common resources, and thus for a strengthened local governance.